Surgical Site Infections: A Still Ongoing Challenge - Rodrigo, A. S. Sardenberg; Riad, N. Younes (International Journal of Infection Prevention, 2019)
Surgical site infections (SSI) have a high incidence, accounting for 20% of all hospital-acquired in-fections. Surgical site infections are linked to a increased length of stay and the risk of mortality. Although most patients recover from an SSI, 77% of mortality can be attributed to the infection it-self 14. The incidence of SSI is 2% to 5% undergoing inpatient surgery 1. Estimated annual in-cidence varies, but may range from 160,000 to 300,000 in the US 14. These estimates might be understated, given the surveillance failure after discharge
Keywords: uperficial infections; deep infections